Visceral Leishmaniasis in Bolivia: Current Status - Mollinedo, Juan Sergio (2020)
Introduction: In Bolivia, before 1982 there were no records of visceral leishmaniasis (VL) cases that would allow us to review and describe the temporospatial occurrence of VL by ecoregions in provinces and departments of Bolivia to evaluate its impact on public health, risk of outbreaks, or dispersion. Methods: This update on VL in Bolivia is based on research, reviews, and retrospective literature analyses of online data and libraries and institutional reports, from 1939 to the present. Results: In Bolivia, 56 cases of VL have been reported. Until 2014, only three endemic departments had been identified (La Paz, Santa Cruz, and Tarija). Since then, further cases have been recorded in Pando, Cochabamba, and Beni, and in Chuquisaca in 2015. In Yungas, a VL focus was confirmed by isolating and comparing parasites from human and dog cases, and from the Lu. longipalpis vector. VL cases from seven departments, involving 12 different ecoregions were located within the Amazon and Plata basins. Conclusions: We confirmed that dogs are its primary reservoir, and Lutzomyia longipalpis is its main vector (currently dispersed in six departments). The primary vectors in areas where Lutzomyia longipalpis is absent are Migonemyia migonei and Lutzomyia cruzi.